ISLAMIC GREEN ECONOMY: A BIBLIOMETRIC ANALYSIS - Atiah, Isti Nuzulul; Pratama, Amelia; Shabrina, Firnanda Maulidya; Muflihah, Inaayatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The ecological crisis has an impact on economic lines in various countries in the world. The concept of green economy exists to mitigate the comprehensive and unified in dealing with the climate crisis and ecological crisis. The concept of green economy was in line with the value in the principles or concepts of Islamic finance. This study aims to identify and analyze research trends with theme Islamic green economy. The data source in this research was taken from the Scopus database, by input the keywords "Green Economy" OR "Islamic Economy" AND "Islamic Green Economy" into the document search field. As a result, 10 journal articles relevant to the research topic were found. Research using VOSviewer indicates a limited body of literature on the Islamic green economy, comprising 10 articles from 2019 to 2024 in Scopus. Contributions spanned countries like Indonesia, Malaysia, the United States, Pakistan, and Qatar, with Qatar pioneering early research and the United States leading in publications. Despite geographic diversity, there's a notable lack of collaboration. The Accounting Research Institute at Universiti Teknologi MARA, Malaysia, initiated research. Co-occurrence analysis revealed 34 keywords in five clusters, focusing on themes like Islamic Social Capital, Maqasid Shariah, and Zakat. Density visualization indicates that topics such as green economy and green sukuk are frequently explored in the literature.